2002
DOI: 10.1021/bi015931h
|View full text |Cite
|
Sign up to set email alerts
|

Protein Conformations Explored by Difference High-Angle Solution X-ray Scattering:  Oxidation State and Temperature Dependent Changes in Cytochrome C

Abstract: We demonstrate the use of high-angle X-ray scattering to explore protein conformational states in solution by resolving oxidation state- and temperature-dependent changes in the conformation of horse heart cytochrome c. Several detailed models exist for oxidation-dependent changes in mitochondrial class I c cytochromes determined by X-ray crystallography and solution NMR techniques. These models differ in the magnitude and locations of structural change. Our scattering measurements show that high-angle X-ray s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
63
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 48 publications
3
63
0
Order By: Relevance
“…(12), sometimes improves comparisons between predicted and experimental scattering profiles. 13,54 As pointed out by Moore, 55 the B-factor is only a rough guide to thermal disorder in solution, at least because B-factors are usually obtained from crystallography and are not necessarily comparable to solution scattering. In addition, correlated thermal motions (not modeled by Debye-Waller factors) contribute to scattering in solution.…”
Section: Effects Of Thermal Disordermentioning
confidence: 99%
“…(12), sometimes improves comparisons between predicted and experimental scattering profiles. 13,54 As pointed out by Moore, 55 the B-factor is only a rough guide to thermal disorder in solution, at least because B-factors are usually obtained from crystallography and are not necessarily comparable to solution scattering. In addition, correlated thermal motions (not modeled by Debye-Waller factors) contribute to scattering in solution.…”
Section: Effects Of Thermal Disordermentioning
confidence: 99%
“…Recently, a number of reports have shown that wide-angle x-ray scattering provides a direct measure of macromolecular conformation in solution (9)(10)(11)(12)(13)(14)(15). Wide-angle x-ray scattering measures rotationally averaged molecular diffraction.…”
mentioning
confidence: 99%
“…Solution x-ray diffraction (SXD) patterns provide one-dimensional (1D) ''fingerprints'' of 3D structure that are directly relatable to atomic configuration by Fourier transform (14)(15)(16)(17). In previous work, we demonstrated that SXD patterns have sufficient resolution to characterize protein and DNA conformations in solution and to discriminate between close but distinguishable crystallographic and NMR models (11,15). Observed broadening of the SXD features compared with those calculated from static structures further indicated that experimental SXD patterns include information on configurational landscapes in solution that can be parameterized in terms of a mean configuration and breadth of the dispersion (14,15).…”
mentioning
confidence: 99%
“…The method of calculating scattering patterns using atomic coordinates was first developed by Svergun et al, 9 and was extended to produce accurate calculation of scattering patterns in high angle region using numerical precision. 14,15 In this approach, protein scattering is calculated from average of partial scattering amplitudes from the fixed atomic coordinated in the molecules, A a , and the solvent excluded volume, A s…”
Section: Methodsmentioning
confidence: 99%
“…e-mail: Hyotcherl.Ihee @kaist.ac.kr tron sources are sensitive to protein conformation states, 14 but also that the measured scattering patterns can be compared quantitatively with calculated patterns from detailed structural models. 14,15 If the time-resolved X-ray wide angle scattering is realized in solution, it will have many advantages over the timeresolved X-ray crystallography. First, it does not require highly-diffracting crystals and this will widen its applicability to a variety of systems.…”
mentioning
confidence: 99%